Book Review of "The Helping Relationship: Healing and Change in Community Context" - Kinzel, Audrey (Canadian Journal of Counselling and Psychotherapy, 2012)
The Helping Relationship presents a variety of topics carefully chosen to give the reader compelling material related to helping clients. The authors represent a range of professions including psychology, psychiatry, and pastoral counselling. Together they offer insights based on original research, clinical experience, and personal theory. Topics key to psychotherapy include transference and countertransference, supervision, and mentoring. The current trend toward manualized therapy and empirically supported treatments are discussed in the context of the helping relationship. Overall, The Helping Relationship provides a range of material related to the reason for the helping relationship: that is, to help the client.